Pengaruh Mulsa Serbuk Gergaji dan Pupuk Npk Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Fase Main Nursery - Fernando Situmorang; Hapsoh '; Gulat ME Manurung (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT This study aimed to determine the effect of sawdust mulch and NPK fertilizer giving on the growth of oil palm seedlings and to get the appropriate dose for the growth of oil palm seedlings. This study has been conducted at the Experimental Garden Faculty of Agriculture, University of Riau began in December 2012 until March 2013. The research was conducted in the experiment form with Completely Randomized Design ( CRD ) which is arranged in factorial consisting of 2 factors, they are: First factor is the standard dose of NPK Sigifertilizer which is consisting P0=Without NPK fertilizer/polybag, P1=NPK dose 2 tablets/polybag, P2=NPKdose 4 tablets/polybag, and P3=NPK dose 6 tablets/polybag. Second factor is the giving of sawdust mulch consisting of M0=Without sawdust /polybag, M1=dose giving sawdust 100 g/polybag, M2=dose giving 200g/polibag sawdust and repeated 3 times, so it can be 36 units in the trial. Each experimental unit consisting of 2 oil palm seedlings, so it takes 72 seeds. The parameters were observed are the plants gain height, increasing number of leaves, increasing tuber diameter, root volume, dry weight seedling and relative growth rate. NPK fertilizer giving gave significantly different effect on seedling height parameter and the number of leaves but did not give significant effect on tuber diameter, root volume, dry weight seedlings and relative growth rate. The combination of sawdust mulch giving 200 g/polybag with NPK fertilizer 4 tablets/polybag give the best seedling growth on the parameters of seedling height, leaf number, root volume and dry weight. Keywords : palm seeds, sawdust mulch, fertilizer NPK